DUTIES AND FUNCTIONS ANALYSIS ABOUT COMMUNITY EMPOWERMENT INSTITUTION IN BONTANG CITY - Hairunnisa Hairunnisa (Spirit Publik: Jurnal Administrasi Publik, 2015)
Institute for Community Empowerment (Lembaga Pemberdayan Masyarakat – LPM) has been established in Bontang City area since 2001 and strengthened by Regional Regulation No. 12 of 2003 on the Institute for Community Empowerment and RT in Bontang City area. This paper aimed to describe the presence of LPM in bringing progress to the Bontang city development. There are four sectors that receive equal attention from the LPM, which includes the religious, infrastructure development, human resources and economics. To develop those four sectors LPM has several functions, consist of: fertilizing sense of unity and cohesion function, coordination plan and perform function, coordination and plan of social institutions function, and utilization of public funds for rural development function. The first three functions had been implemented well, while the last function was implemented quite well. However there were concerns about the process of development planning where participatory approach was not all active. Having this results, it can be conclude that the presence of LPM has positively influence the development in Bontang City. Keywords : Community Empowerment Institution.